Implicature as Social Criticism of Asian American Stereotypes in Jimmy O. Yang’s Stand-Up Comedy - Dio Alif Dwitama; Dadan Rusmana; Ice Sariyati (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2026)
This study examines how pragmatic violations in stand-up comedy function as a strategy for social criticism, focusing on Jimmy O. Yang’s performances in Good Deal (2020) and Guess How Much (2023). The research aims to identify the types of conversational maxims flouted and to analyze how the resulting implicatures challenge dominant Asian American stereotypes. Using a qualitative approach with a data condensation method, this study applies Grice’s (1975) cooperative principle to classify maxim violations and employs intersectional sociological frameworks to interpret their critical meanings. The analysis identifies 79 utterances containing conversational implicatures that function as social critique. The findings show that the maxim of Quality is the most frequently flouted, with 56 occurrences, mainly through irony and hyperbole to produce cognitive incongruity. These pragmatic violations are consistently directed at four dominant stereotypes: the perpetual foreigner label (27 occurrences), economic stereotypes related to immigrant frugality (21 occurrences), the emasculation of Asian men (16 occurrences), and the model minority myth (15 occurrences). These results demonstrate that maxim flouting operates as a systematic linguistic strategy rather than a purely comedic device. Yang uses implicature to expose contradictions within hegemonic narratives and to challenge Eurocentric perspectives on Asian American identity. This study suggest that stand-up comedy can function as a form of socio-political discourse, where pragmatic non-observance serves as an effective tool for resistance and identity reconstruction.